Assessing the completeness of death data and its impact on life expectancy gender gap, case of Albania - Nesturi, Majlinda (European Journal of Multidisciplinary Studies, 2023)
Estimates of completeness of death registration are crucial to estimate the usual resident population in the country as well as to produce estimates of life tables and population forecasts. Moreover, timely and reliable data on deaths are fundamental for informed decision-making in the health sector. Measurements of completeness of death registration provide timely and locally relevant feedback on system performance and can guide interventions to strengthen and improve Civil Registration System of Vital Statistics performance over time. This paper aims to give an overview of the estimates of the completeness of death data in Albania, detailing it further considering the age, sex characteristics by applying indirect method using official data. All the studies done so far, show that on national level there is an under coverage of the total number of deaths, which depending on the approach used, figure out an improvement of the death registration in Albania over the years. However, the findings of our analysis considering the age and sex dimensions show that still there exists an under coverage of female deaths, more evident in older ages. The adjusted life expectancy showed an improvement in the life expectancy gender gap. The results of this paper can be used to derive adjusted sex-age specific death rates, as far as the results allow doing so, in order to provide more accurate calculation of life expectancy, mortality and population forecasts.